EFFECTS OF ACUTE EXERCISE ON SERUM BDNF LEVEL IN PATIENTS WITH RHEUMATOID ARTHRITIS - Yentur, S. Baglan; Ercan, Z.; Deniz, G.; Karatas, A.; Gur, M.; Alkan, G.; Koca, S. S. (Elsevier, 2021)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 02-05, 2021 -- ELECTR NETWORK